TRANSFORMING GROWTH FACTOR 1 IN CHILDREN OF EARLY AGE WITH LIVER TRANSPLANTATION - R. M. Kurabekova; O. P. Shevchenko; O. M. Tsiroulnikova; I. E. Tsiroulnikova; G. A. Olefirenko; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Transforming growth factor β1 (TGF-β1) plays a key role in the development of the immune response, as well as in the process of liver regeneration. Measuring the level of TGF-β1 may have important clinical implications in liver transplantation, because cytokine concentration in the tissue and in blood plasma varies with different liver diseases. Aim. To analyze the dynamics of TGF-β1 levels in children-recipients with liver transplant from related donors, including from incompatible blood groups.Materials and methods. The study involved 127 children aged 3 to 72 months (median – 8, average age – 12 ± 14 months), including 57 boys and 70 girls, with liver cirrhosis, developed as the result of congenital and hereditary diseases of the hepatobiliary system. All patients underwent transplantation of the left lateral liver sector from living related donors: 98 patients were transplantedfragment of a liver from identical or AB0-compatible donors and 29 – from incompatible donors. The concentration of TGF-β1 was determined by enzyme immunoassay method in blood plasma samples.Results. Average level of TGF-β1 in blood plasma of children with liver cirrhosis, developed as the result of congenital and hereditary diseases of the hepatobiliary system was 5,2 ± 5,5 ng/ml. A month after liver transplantation from a related donor level of TGF-β1 in blood plasma of recipients increased to 8,1 ± 9,6 ng/ml. One year after transplantation, the average level of TGF-β1 in the recipients of liver fragment was 7,7 ± 8,4 ng/ml, and signifi cantly (p = 0,00) differed from the level prior to transplantation. No association between TGF-β1 level in a month and a year after transplantation and the compatibility of the recipient with AB0 donor was found. A correlation (r = –0,23, p < 0,05) between level of TGF-β1 prior to transplantation and the development of graft dysfunction was observed: in recipients with graft dysfunction (16 cases) cytokine level prior to surgery was lower (p = 0,047) than in other recipients.Conclusion. Liver transplantation leads to a signifi cant increase in the level of TGF-β1 in the blood plasma of children and that level is not different in recipients after transplantation of a liver fragment from AB0-compatible and AB0-incompatible donors and in recipients with anti-group antibodies before and/or after transplantation, and without them.